2022
DOI: 10.3390/su14138169
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Innovative Performance of Renewable Energy Enterprises in China: Effects of Subsidy Policy and Intellectual Property Legislation

Abstract: Energy efficiency and emissions reductions are effective initiatives to address climate change and energy security. China has increased government subsidies and intellectual property protection (IPP) intensity to promote technological innovation in the renewable energy sector. This paper selects samples of geothermal, wind, and solar energy companies and examines whether the two initiatives mentioned above can improve company innovation, and assesses their action pathways. The results reveal that: (i) governme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…Energy efficiency innovation can be used to reduce emissions that cause climate change and provide energy security. Countries like China have increased government subsidies as high as 40 % and intellectual property protection to promote technological innovation in the renewable energy sector [ 78 ]. It was shown that investment in energy-efficient innovation is not sustainable without appropriate protection for invention or innovation.…”
Section: Analysis Of Energy-efficient Innovation Laws In Saudi Arabiamentioning
confidence: 99%
See 1 more Smart Citation
“…Energy efficiency innovation can be used to reduce emissions that cause climate change and provide energy security. Countries like China have increased government subsidies as high as 40 % and intellectual property protection to promote technological innovation in the renewable energy sector [ 78 ]. It was shown that investment in energy-efficient innovation is not sustainable without appropriate protection for invention or innovation.…”
Section: Analysis Of Energy-efficient Innovation Laws In Saudi Arabiamentioning
confidence: 99%
“…The IP legislation should match the country's technological capacity and economic base which should avoid excessive legislation. Organizing IP publicity and training will attract more innovators [ 78 ].…”
Section: Policy and Legal Measures To Foster Energy Efficient Innovat...mentioning
confidence: 99%
“…As patent authorization is a direct indicator of a region's capacity for scientific and technological innovation, according to the approach of Xu et al [55], this study uses a logarithmic formula to evaluate the extent of regional intellectual property protection by calculating the annual patent authorization of the provincial administrative region where the enterprise is enrolled.…”
Section: (4) Moderator Variable: Intensity Of Intellectual Property P...mentioning
confidence: 99%
“…This is helpful to preserve the enterprise group's effective financial allocation and to lower financial waste. In addition, adequate R&D funding can boost organizations' innovation output, which in turn influences their innovation efficiency [35]. Therefore, the enterprise group has a positive influence on innovation efficiency through the internal capital market path.…”
Section: Internal Capital Market Impact Pathmentioning
confidence: 99%